From Librametry to Webometric Research in India With Emphasis on the Work Done Since 2001 - Ravichandra Rao, I. K. (Journal of Information and Knowledge, 2013)
A survey of scientometric literature of India for the period 2000-12 was carried out to study and understand scientometric research in India. The data were collected from LISA; 175 documents are covered in this survey. most of which were published in Annals of Library and Information Science, SRELS Journal of Information Management, DESIDOC Bulletin of Information Technology, COLLNET Journal of Scientometrics and Information management and Journal of Scientometrics. Discussions in the reviewed papers relate to several topics in scientometrics – India’s contribution to world literature, growth of Indian literature, proportion of collaborative research, etc. This review indicates that the Indian publications are now visible and it is increasing, There is hardly any research being done to evaluate and measure research outcome; there is also no evidence that the results of the scientometric research is being used in drafting science policy or in science administration.